Socio-Cultural Based Religious Moderation in the Millennial Generation - Swarizona, Silkania; Widodo, Bambang Sigit; Hilmi, Ahmad Nizar; Huda, Mi’rojul; Pasu, Iman (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2025)
Religious moderation is a concept that emphasizes the importance of balance, tolerance and avoiding extremism in religion. This research focuses on the implementation of socio-cultural-based moderation in Watutulis Village, Prambon District, Sidoarjo Regency, East Java, which is designated as a Pancasila Pilot Village. The millennial generation in this village plays an important role in strengthening the values of diversity through preserving local traditions and using digital technology. This research uses a qualitative approach with a case study method. The research results show that local traditions such as Sedekah Bumi, Pancasila-based digital literacy, and national workshops play a significant role in promoting religious moderation. Theories of religious and socio-cultural pluralism are used as an analytical framework in understanding the context of this research.